'Out in the middle'. Humanities, interdisciplinary and the post-graduate puzzle: An interview with Professor Wiljan van den Akker. (February 2020) - Vale, Peter
Wiljan van den Akker is a university professor, a respected academic administrator, and a published poet and writer. From a base at the Utrecht University, in the Netherlands, his three-decade long career spans three continents and includes one-on-one associations with Berkeley, UCLA and Oxford. Currently, he is the Vice-Rector for Research at Utrecht but retains the title he was awarded in 2003, Distinguished Professor of Modern Poetry. In early June 2015, Peter Vale interviewed van den Akker in his house in Jeruzalemstraat, Utrecht. This is an edited version of two conversations.